Presoja dokaznih predlogov v upravnem sporu - Žuber, Bruna (Pravnik, 2023)
Administrative dispute is evolving towards a more proactive role for the administrative court in determining the relevant facts and legal basis of the case. Despite the possibility for the court to take evidence ex officio in administrative dispute, the bulk of the activity of taking evidence rests with the parties to the proceedings. It is for the court to assess the evidence presented and to decide on the admissibility of specific pieces of evidence. This article deals with the assessment of motions for evidence in administrative dispute. It first discusses the meaning and exercise of the right to evidence and the related distribution of the burden of proof in administrative dispute. It then focuses, from a theoretical and practical perspective, on the assessment of submitted evidence in administrative dispute, distinguishing between formal and substantive criteria for assessing the admissibility of submitted evidence. The article also analyses the use of evidence obtained in violation of human rights and freedoms, examines the assessment of evidence in the context of the decision to issue an interim injunction, and analyses the standards of reasoning applied in the dismissal of evidence.
Keywords: administrative dispute; burden of proof; criteria for assessing the admissibility of proposed evidence; dokazni predlog; dokazno breme; formal criteria; formalna merila; materialna merila; merila presoje dopustnosti dokaznega predloga; pravica do dokaza; proposed evidence; right to evidence; substantive criteria; upravni spor